Identificaton of grouper parasites (Epinephelus coioides) in Talawi District, Batubara Regency - Rumondang Rumondang; Harmayani Harmayani; Heri Prasuhandra Manurung; Adlidar Putri; Ingka Sari (Depik, 2022)
Batu Bara Regency is a region with abundant natural resources, one of which is the cultivation of grouper fish. Grouper is a member of the Serranidae family of coral reef fish. Many groupers are raised in ponds, which makes them susceptible to disease due to environmental and dietary factors that are not adapted to grouper fish, which is a native species. Parasites are one of the grouper-infecting diseases that, if left untreated, can result in mass mortality and harm farmers. The aim of this study was to identify parasites in ponds in Mesjid Lama Village, Talawi District, so that it would be easier to determine the type of parasite, its level of attack, and subsequent efforts to eradicate it. This research employs a sampling technique, specifically a random sampling of orange-spotted grouper. The results of the performed analysis include analyses of both ectoparasites and endoparasites. Several types of ectoparasites were identified, including Cryptocaryon irritans, Pseudorhabdosynochus sp, Benedenia epinepheli, and Caligus sp, while Prosorynchus sp was identified as the endoparasite. The most prevalent parasite found in the fish is Cryptocaryon irritans.Keywords: EndoparasiteParasitesGrouper